2005
DOI: 10.1007/s11136-004-2580-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lipodystrophy-associated body changes and measures of quality of life and mental health for HIV-positive adults

Abstract: Although responsive to the total symptom profile, psychosocial measures typically utilized for evaluating quality of life and mental health status in HIV disease lacked sensitivity and specificity for measuring the consequences of lipodystrophy-associated fat distribution changes alone. Lipodystrophy severity did impact negatively on body image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 35 publications
2
32
0
5
Order By: Relevance
“…Even though the sample size was small, men scored lower on negative mood and homosexual men scored lower on psychological functioning. On a subsample of this study 8 applying a different questionnaire, Blanch and coauthors 9 found that changes in the breast, face, or legs were significantly associated with greater impairment of psychosocial functioning. In the multivariate analysis only changes in the breast remained significant.…”
Section: Lipodystrophy and Quality Of Life 581mentioning
confidence: 78%
See 1 more Smart Citation
“…Even though the sample size was small, men scored lower on negative mood and homosexual men scored lower on psychological functioning. On a subsample of this study 8 applying a different questionnaire, Blanch and coauthors 9 found that changes in the breast, face, or legs were significantly associated with greater impairment of psychosocial functioning. In the multivariate analysis only changes in the breast remained significant.…”
Section: Lipodystrophy and Quality Of Life 581mentioning
confidence: 78%
“…6,7 Few studies have addressed quality-of-life issues in HIVinfected patients with LD, and its impact has not been es-tablished definitively. Some studies demonstrating effects have used instruments not widely validated in people with HIV infection, 8,9 while others have failed to find correlations with health-related quality of life. 10,11 The main objective of this study was to identify the impact of LD on the health-related quality of life in HIV-infected people taking HAART.…”
mentioning
confidence: 99%
“…Alterations in body image faced by persons taking ART can have repercussions on affective and emotional health. Low self-esteem, poor body image, and depression have been associated with LS (Bourgoyne et al, 2005;Peterson et al, 2008). Despite the benefits of ART, treatment may, ironically, reduce quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-infected individuals with HAART-related lipodystrophy are significantly more likely than HIV-infected individuals without HAART-related lipodystrophy to report body image dissatisfaction [28][29][30][31][32]. Lipodystropy is associated with diminished self-esteem and depression, fear of stigmatization, problems with dressing and social isolation [18].…”
Section: Consequencesmentioning
confidence: 99%